Combinatorial Crispr/Cas9 For Suppression Of Latent Hiv-1 Provirus In Vitro - Ravichantar, Nithya (2020)
Although HAART effectively suppresses HIV-1 replication, its compromised effectiveness against non-B subtypes, the challenge of eliminating latent proviruses, life-long treatment, and viral resistance complicates the cure for HIV-1. CRISPR/Cas9, the latest genome editing tool, can overcome the limitations seen with HAART. By targeting the promoter of HIV-1 (LTR), CRISPR/Cas9 can disrupt the latent reservoirs. Here, we designed an improved CRISPR/Cas9 system, combinatorial CRISPR/Cas9 to concurrently knockdown multiple HIV-1 genes: structural (Pol and Gag), regulatory (Rev and Tat) and accessory genes (Vif). We investigated the efficacy of this tool as a therapy against different viral subtypes in a subset population . Our preliminary data, showed a huge decrease in viral load and we verified the safety of CRISPR/Cas9 in human cell lines.